2023
DOI: 10.1111/eva.13625
|View full text |Cite
|
Sign up to set email alerts
|

A cytochrome P450 insecticide detoxification mechanism is not conserved across the Megachilidae family of bees

Angela Hayward,
Benjamin J. Hunt,
Julian Haas
et al.

Abstract: Recent work has demonstrated that many bee species have specific cytochrome P450 enzymes (P450s) that can efficiently detoxify certain insecticides. The presence of these P450s, belonging or closely related to the CYP9Q subfamily (CYP9Q‐related), is generally well conserved across the diversity of bees. However, the alfalfa leafcutter bee, Megachile rotundata, lacks CYP9Q‐related P450s and is 170–2500 times more sensitive to certain insecticides than bee pollinators with these P450s. The extent to which these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 119 publications
0
2
0
Order By: Relevance
“…In contrast, some wild species, i.e. species from the Megachilini, Lithurgini and Anthidini tribes (Megachilidae family), lack CYP9Q-related P450s and have been shown to be more sensitive to neonicotinoid thiacloprid and imidacloprid insecticides (Hayward et al 2024 , 2019 ). However, it has been hypothesized that these deficits in detoxification genes would increase bee sensitivity to interactions among toxicants (Berenbaum and Johnson 2015 ), which could partly explain our results with a single molecule exposure.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, some wild species, i.e. species from the Megachilini, Lithurgini and Anthidini tribes (Megachilidae family), lack CYP9Q-related P450s and have been shown to be more sensitive to neonicotinoid thiacloprid and imidacloprid insecticides (Hayward et al 2024 , 2019 ). However, it has been hypothesized that these deficits in detoxification genes would increase bee sensitivity to interactions among toxicants (Berenbaum and Johnson 2015 ), which could partly explain our results with a single molecule exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Today we also know that gene family changes have had major implications in the evolution of herbivory within Drosophilidae [ 30 ]. More recently, an interesting research on gene families in megachilid bees showed that the species of the tribes Osmiini and Dioxyni have certains CYP9Q-related P450 enzymes that are able to detoxify the neonicotinoid insecticide thiacoprid, unlike their close relatives of the tribe Megachilini [ 31 ].…”
Section: Introductionmentioning
confidence: 99%